Effect of Glucose on the Synthesis of Iron Carbide Nanoparticles from Combustion Synthesis Precursors. Issue 4 (1st February 2016) - Gu, Yueru; Qin, Mingli; Cao, Zhiqin; Jia, Baorui; Wang, Xuanli; Qu, Xuanhui
Abstract : Iron carbide (Fe3 C) nanoparticles have been successfully synthesized by combining low‐temperature combustion synthesis method with carbothermal reduction. A homogeneous precursor powder (Fe2 O3 + C) derived from iron nitrate, glycine, and glucose mixed solution was subsequently calcined under nitrogen at 450°C–700°C for 2 h. Effects of glucose on the size and morphology of the precursors as well as the synthesized Fe3 C powders were studied in details. The results showed a regular variation in the particle size and morphology of the precursors and Fe3 C powders with the increasing molar ratio of glucose to iron nitrate (G/Fe). XRD analysis indicated that the initial transformation of the precursor for (G/Fe = 1) to Fe3 C occurred at 500°C. Meanwhile, magnetic properties of the Fe3 C have been tested by vibrating sample magnetometer (VSM). The saturation magnetization (Ms) of Fe3 C powders synthesized using different G/Fe ratios (G/Fe = 1, 2, 3) was 51.2, 37.0, and 27.1 emu/g, respectively. This made the Fe3 C a promising candidate for magnetic materials.